Large eddy simulations (LES) of inclined dense jets in coastal waters - Zhang, Shuai (2016)
Desalination plants are increasingly common to augment the freshwater supply to ease the pressure on the demand of freshwater due to the rapid global urbanization. In view of potential environmental impacts, the brine outfall of desalination plants must be properly designed to ensure good mixing with the surrounding ambient seawater. Many previous studies had been performed experimentally on the mixing behavior of inclined dense jets, and analytical models had also been developed based on these experimental results to aid the outfall design. However, the accuracy of predictions by these models still needs further improvement. The Computational Fluid Dynamics (CFD) approach offers another alternative to predict the mixing behavior of inclined dense jets in coastal waters. So far, only a few CFD studies using the Reynolds Averaged Navier-Stokes (RANS) approach have been reported in the literature. In the present study, the mixing behavior of the inclined dense jet is investigated with the Large Eddy Simulation (LES) approach, which is theoretically more advanced in terms of resolving the large coherent eddies involved.